2022
DOI: 10.3389/fendo.2022.893678
|View full text |Cite
|
Sign up to set email alerts
|

The Role of SIRT3 in the Osteoporosis

Abstract: SIRT3 is an NAD+-dependent deacetylase in the mitochondria with an extensive ability to regulate mitochondrial morphology and function. It has been reported that SIRT3 participates in the occurrence and development of many aging-related diseases. Osteoporosis is a common aging-related disease characterized by decreased bone mass and fragility fractures, which has caused a huge burden on society. Current research shows that SIRT3 is involved in the physiological processes of senescence of bone marrow mesenchyma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 121 publications
0
8
0
Order By: Relevance
“…Similarly, a previous study demonstrates that SIRT5 deletion promotes obesity-associated osteoarthritis development [ 24 ]. In addition, the role of other members of the SIRT family in bone-related diseases has also been described [ 26 , 27 ]. Interestingly, we found that low level of SIRT5 was also associated with tumors that are not primary chordoma (6 out of 13), suggesting that other primary tumors may have a low level of SIRT5 or that other primary tumors may have a high level of SIRT5 while the SIRT5 level was decreased when progressing and metastasizing.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a previous study demonstrates that SIRT5 deletion promotes obesity-associated osteoarthritis development [ 24 ]. In addition, the role of other members of the SIRT family in bone-related diseases has also been described [ 26 , 27 ]. Interestingly, we found that low level of SIRT5 was also associated with tumors that are not primary chordoma (6 out of 13), suggesting that other primary tumors may have a low level of SIRT5 or that other primary tumors may have a high level of SIRT5 while the SIRT5 level was decreased when progressing and metastasizing.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoporosis is a common aging-related disease characterized by decreased bone mass and fragility fractures, and places a huge burden on society ( Hu and Wang, 2022 ). The kl/kl mice exhibit a state of low turnover involving formation and resorption of bone, similar to humans ( Kuro-o et al, 1997 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mice lacking SIRT3 have significantly shortened lifespans (Benigni et al, 2019 ) and spontaneously develop aging‐related diseases. Deletion of SIRT3 has a deleterious effect on mitochondrial biogenesis and function, which plays an important role in several age‐related diseases (Cao, Zhao, et al, 2022 ; Hu & Wang, 2022 ). Increased SIRT6 activity also correlates with increased lifespan among species, a phenotype attributed to its effect on protection from DNA damage (Korotkov et al, 2021 ; Taylor et al, 2022 ; Tian et al, 2019 ).…”
Section: Nad Metabolism In Agingmentioning
confidence: 99%